Swimming speed alteration in the early developmental stages of Paracentrotus lividus sea urchin as ecotoxicological endpoint. (April 2016) - Morgana, Silvia; Gambardella, Chiara; Falugi, Carla; Pronzato, Roberto; Garaventa, Francesca; Faimali, Marco
Abstract: Behavioral endpoints have been used for decades to assess chemical impacts at concentrations unlikely to cause mortality. With recently developed techniques, it is possible to investigate the swimming behavior of several organisms under laboratory conditions. The aims of this study were: i) assessing for the first time the feasibility of swimming speed analysis of the early developmental stage sea urchin Paracentrotus lividus by an automatic recording system ii) investigating any Swimming Speed Alteration (SSA) on P. lividus early stages exposed to a chemical reference; iii) identifying the most suitable stage for SSA test. Results show that the swimming speed of all the developmental stages was easily recorded. The swimming speed was inhibited as a function of toxicant concentration. Pluteus were the most appropriate stage for evaluating SSA in P. lividus as ecotoxicological endpoint. Finally, swimming of sea urchin early stages represents a sensitive endpoint to be considered in ecotoxicological investigations. Highlights: The swimming speed of embryos and larvae of P. lividus was measured through SBR system. Swimming speed was inhibited in embryos and larvae exposed to CdCl2 . The behavioral bioassay is more sensitive than the acute test.